Measuring prefrontal cortical activity during dual task walking in patients with Parkinson's disease: feasibility of using a new portable fNIRS device. Issue 1 (December 2016) - Nieuwhof, Freek; Reelick, Miriam; Maidan, Inbal; Mirelman, Anat; Hausdorff, Jeffrey; Olde Rikkert, Marcel; Bloem, Bastiaan; Muthalib, Makii; Claassen, Jurgen
Abstract Background Many patients with Parkinson's disease (PD) have difficulties in performing a second task during walking (i.e., dual task walking). Functional near-infrared spectroscopy (fNIRS) is a promising approach to study the presumed contribution of dysfunction within the prefrontal cortex (PFC) to such difficulties. In this pilot study, we examined the feasibility of using a new portable and wireless fNIRS device to measure PFC activity during different dual task walking protocols in PD. Specifically, we tested whether PD patients were able to perform the protocol and whether we were able to measure the typical fNIRS signal of neuronal activity. Methods We included 14 PD patients (age 71.2 ± 5.4 years, Hoehn and Yahr stage II/III). The protocol consisted of five repetitions of three conditions: walking while (i) counting forwards, (ii) serially subtracting, and (iii) reciting digit spans. Ability to complete this protocol, perceived exertion, burden of the fNIRS devices, and concentrations of oxygenated (O2 Hb) and deoxygenated (HHb) hemoglobin from the left and right PFC were measured. Results Two participants were unable to complete the protocol due to fatigue and mobility safety concerns. The remaining 12 participants experienced no burden from the two fNIRS devices and completed the protocol with ease. Bilateral PFC O2 Hb concentrations increased during walking while serially subtracting (left PFC 0.46 μmol/L, 95 % confidence interval (CI) 0.12–0.81, right PFC 0.49 μmol/L, 95 % CI 0.14–0.84) and reciting digit spans (left PFC 0.36 μmol/L, 95 % CI 0.03–0.70, right PFC 0.44 μmol/L, 95 % CI 0.09–0.78) when compared to rest. HHb concentrations did not differ between the walking tasks and rest. Conclusions These findings suggest that a new wireless fNIRS device is a feasible measure of PFC activity in PD during dual task walking. Future studies should reduce the level of noise and inter-individual variability to enable measuring differences in PFC activity between different dual walking conditions and across health states.